Importance and ILL-Effects of Nanoparticles: Sensors for their Identification - Krishnamurthy, Vallidevi; Gopinath, Kannapan P.; Gnanaprakash, Dhakshinamoorthy; Vanathi, Ganeshraj; Shivanirudh, Suresh Ganapathy; Ahamed, Mohd Imran (Current Analytical Chemistry, 2021)
Background: Nanoparticles have become an important part of many modern scientific technologies. Also, many naturally occurring nanoparticles play an important role in various natural and synthetic processes. The detection of these nanoparticles is expensive and challenging. This review paper explains in detail about various sensor-based methods used for the detection of nanoparticles. Methodology: Sensor-based analytical techniques are more accurate than other techniques. Nanoparticles may occur in air, water, solid surface and human or other living organisms’ physical environments. The detection methods include spectroscopic techniques, electrochemical methods, microcavities and microlasers based detection, optical techniques and many other highly sensitive methods. All these methods and their principles are explained in this study. The importance and the ill effects of the nanoparticles are explained in this article. Further, the detection of a particular single nanoparticle is also discussed. Conclusion: The detailed comparative analysis of these methods has shown that sensor-based methods are highly efficient for the detection of nanoparticles. Further research in this field may introduce many cost-effective and high efficient detection techniques that would revolutionize the medical and other application fields.
Keywords: microcavities and microlasers based detection